Bureaucratic Ethics in the Era of Technological Disruption: Challenges and Strategies for Bureaucratic Reform 4.0 - Hutauruk, Rosinta Paulina; Fahmi, Ade; Maulana, Dimas Gilang (JURNAL SOSIAL DAN HUMANIS SAINS, 2021)
This study explores the evolving landscape of bureaucratic ethics in the context of technological disruption, particularly within the framework of Bureaucratic Reform 4.0. As governments adopt digital technologies to improve efficiency and responsiveness, they face complex ethical challenges related to data governance, algorithmic accountability, and public trust. Using a qualitative descriptive method, this research combines document analysis and in-depth interviews with public officials and digital governance experts to examine ethical risks and institutional responses. The findings reveal a significant gap between technological innovation and ethical preparedness in many public institutions. Issues such as ethical fatigue, lack of regulatory clarity, and uneven digital capabilities among administrative levels pose serious threats to the integrity of public service. However, the study also highlights the critical role of ethical leadership and institutional commitment in mitigating these challenges. It concludes that bureaucratic reform must not only be technologically driven but also ethically grounded, ensuring that innovation enhances, rather than undermines, democratic governance and public accountability.